THE INFLUENCE OF SOME CLIMATIC FACTORS ON THE EFFECTIVENESS OF ESTRUS SYNCHRONIZATION IN BEEF OF DAIRY COWS - Jumatayeva, K. K.; Julanov, M. N.; Koibagarov, K. U.; Julanova, N. M. (Zkatu im. Zhangirhana, 2024)
The aim of this study was to determine the influence of the temperature humidity index (THI) on the efficiency of estrus synchronization on both beef and dairy cows. The research was carried out at APC "Azamat" of the Beskaragai district of the East Kazakhstan region of the Republic of Kazakhstan. The natural and climatic conditions of this zone make it possible to raise both beef and dairy cattle. The study involved 408 Kazakh white-headed cows aged 3 to 5 year. During the experimental period, the data for air temperature (T), relative humidity (φ), wind speed (υ) were collected, and the temperature humidity index (THI) was determined. The data was recorded for 30 days (10 days before synchronization, 10 days during synchronization and 10 days after synchronization). In addition, during the synchronization period, clinical parameters - body temperature (t), pulse (P), respiratory rate (Re) and rumination (R) were measured daily in 10% of animals by conventional methods. During the experimental period (2020-2022) THI was 74,50±1,31, 78,20±2,11, 72,80±0,7210 days before the estrus synchronization. When THI was increased by 5.6±0.03 in 2021 compared to 2020, the fertility decreased by 9.7±0.78. Similarly, when THI was increased by 7.3 ± 0.56 compared to 2022, fertility was reduced by 13.8 ± 0.36. The latter indicates that when THI increases the fertility rate decreases. Based on the results, there is an influence of THI on the effectiveness of estrus synchronization. Increased THI, to a certain extent, reduces both estrus expression and effectiveness of estrus synchronization leading to reduced fertility rate and increased embryonic mortality.
Jumatayeva, K. K. THE INFLUENCE OF SOME CLIMATIC FACTORS ON THE EFFECTIVENESS OF ESTRUS SYNCHRONIZATION IN BEEF OF DAIRY COWS / K. K. Jumatayeva, M. N. Julanov, K. U. Koibagarov, N. M. Julanova [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-1 (72). Ч. І. - Р. 158-167. - ISSN 2305-9397.
Keywords: Estrus synchronization; cows; artificial insemination; temperature humidity index; зкату; научный журнал